Penerapan Belbin Team Role dalam Mengatasi Ketidaksinkronan Tujuan Tim Pemasaran PT XYZ - Nurmiati, Evy; Shufa, Aliya Nabila; A, Alif Salsabila; Nurzahra, Bevy Annisa; Fauzan, Rizki (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The fast-moving consumer goods (FMCG) sector in Indonesia is experiencing a shift in competitive dynamics, characterized by the impact of digital disruption and evolving consumer behaviors. This scenario necessitates the establishment of a collaborative environment within the marketing team, particularly during the initiation of new product launches. However, in practice, functional conflicts often arise due to a lack of alignment in perceptions of objectives and ambiguity in roles between the Graphic Design Team, which is oriented towards visual creativity, and the Data Analyst Team, which emphasizes data-based validation. These conflicts frequently impede effective decision-making processes and diminish the team's overall performance. The objective of this study is to examine the efficacy of implementing the Belbin Team Role Model as a diagnostic instrument and behavioral intervention to address role conflicts and align perceptions of work objectives within the Marketing Team at PT XYZ.The present study employed a qualitative approach, utilizing an exploratory case study design. The subjects of the research study comprised eight individuals from the Marketing Team at PT XYZ. The data collection techniques employed in this study included the Belbin Self-Perception Inventory (SPI), observational assessments, and in-depth interviews conducted prior to and following the intervention. The data were then subjected to thematic analysis, a method of data interpretation that seeks to identify patterns of conflict, role clarity, and changes in teamwork dynamics. The results of the study indicate an imbalance in the composition of team roles, characterized by the dominance of Plant and Shaper roles and the absence of Monitor Evaluator roles. This imbalance has been shown to trigger conflict between creative and analytical orientations. The application of the Belbin Model has proven effective in providing a neutral role language, increasing role clarity, and transforming dysfunctional conflict into constructive discussion. This intervention has been demonstrated to facilitate the alignment of perceptions regarding team objectives by integrating visual creativity and data validation in a more balanced manner.